2015
DOI: 10.1007/s00221-015-4206-z
|View full text |Cite
|
Sign up to set email alerts
|

Poor motor function is associated with reduced sensory processing after stroke

Abstract: The possibility to regain motor function after stroke depends on the intactness of motor and sensory pathways. In this study, we evaluated afferent sensory pathway information transfer and processing after stroke with the coherence between cortical activity and a position perturbation (position-cortical coherence, PCC). Eleven subacute stroke survivors participated in this study. Subjects performed a motor task with the affected and non-affected arm while continuous wrist position perturbations were applied. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
2
39
1
1
Order By: Relevance
“…Later on, PCC was employed to evaluate ascending somatosensory pathway information transfer in the subacute stroke patients. These results suggested that motor function impairment may company with reduced somatosensory processing after stroke (Campfens et al ., ). Previous studies have indicated that the importance of sensory feedback for motor recovery after stroke (Hamdy et al ., ; Rossini et al ., ).…”
Section: Distinguishing the Motor And Somatosensory Communicationsmentioning
confidence: 97%
“…Later on, PCC was employed to evaluate ascending somatosensory pathway information transfer in the subacute stroke patients. These results suggested that motor function impairment may company with reduced somatosensory processing after stroke (Campfens et al ., ). Previous studies have indicated that the importance of sensory feedback for motor recovery after stroke (Hamdy et al ., ; Rossini et al ., ).…”
Section: Distinguishing the Motor And Somatosensory Communicationsmentioning
confidence: 97%
“…1,2,9 Yet, somatosensory deficits contribute to poor function after stroke, [10][11][12][13] with >50% of stroke survivors having proprioceptive impairments. 14,15 Although these deficits are thought to significantly affect stroke recovery, 10,16 few studies have examined the effect of somatosensory impairments on recovery.…”
mentioning
confidence: 99%
“…The patients might feel tired, anxious, and lose self-confidence. Given that a majority of patients have sensory impairments that give rise to mental health issues, it is valuable to facilitate population's access to sensory intervention such as touch, vision and audiological rehabilitation [86].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory function is an important composition of widely used physiotherapy approaches such as Bobath (known as Neurodevelopment Therapy in the United States) and Brunnstrom, and it is considered a precursor to the recovery of movement and functional activities of daily living in patients with stroke [9]. Poor motor function is associated with reduced sensory experience and processing after stroke [10,11]. Joint position sensation of the upper extremity is closely related to motor ability due to stroke-related reduced discrimination in proprioception [9], it causes disturbances in the arm movement trajectory.…”
Section: Introductionmentioning
confidence: 99%